Phosphodiesterase-5 Inhibitors: Action on the Signaling Pathways of Neuroinflammation, Neurodegeneration, and Cognition - Christina Alves Peixoto; Ana Karolina Santana Nunes; Ana Garcia-Osta (Mediators of Inflammation)
Phosphodiesterase type 5 inhibitors (PDE5-Is) have recently emerged as a potential therapeutic strategy for neuroinflammatory, neurodegenerative, and memory loss diseases. Mechanistically, PDE5-Is produce an anti-inflammatory and neuroprotection effect by increasing expression of nitric oxide synthases and accumulation of cGMP and activating protein kinase G (PKG), the signaling pathway of which is thought to play an important role in the development of several neurodiseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). The aim of this paper was to review present knowledge of the signaling pathways that underlie the use of PDE5-Is in neuroinflammation, neurogenesis, learning, and memory.